Pengaruh Pendekatan Active Learning Dengan Model Pembelajaran Kooperatif Tipe Student Facilitator and Explaining (SFAE) Terhadap Hasil Belajar IPA - nurul akmal; Kamaliansyah Walil (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2021)
English: The study aims to determine the effect of the active learning approach with SFAE type cooperative learning model on science learning outcomes for class IX students of SMP Negeri 14 B. Aceh. This type of research is experimental research. The research design used Posttest-Only Control Group Design. The study population was all students of class IX SMP Negeri 14 B.Aceh. The sampling technique used cluster random sampling where the students of class IX A as the experimental class and class IX B as the control class were obtained. The results showed the average post-test score for the experimental class was 77.5 and for the control class was 54.07. The results of the normality test show that the X2count value is 2.7 for the experimental class and X2count is 2.2 for the control class. The value of X2table is 5.9 at a significant level of 0.05. The value of X2count is less than X2table, then the data is normally distributed. The results of the homogeneity test of the experimental class and the control class showed the F count value of 1.19 and the F table value of 1.85. The value is less than , then the two classes are homogeneous. The results of the pooled variance t-test obtained a t-value of 2.29 and a t-table value of 1.645 with a significant level of 0.05. The value is greater than , then Ho is rejected and Ha is accepted. The conclusion of the study is that there is an effect of the SFAE learning model with an active learning approach on the science learning outcomes of class IX science students at SMP Negeri 14 B. Aceh. Bahasa: Penelitian ini bertujuan untuk mengetahui pengaruh pendekatan active learning dengan model pembelajaran kooperatif tipe SFAE terhadap hasil belajar IPA siswa kelas IX SMP Negeri 14 B. Aceh. Jenis penelitian ini adalah penelitian eksperimen. Populasi penelitian adalah seluruh siswa kelas IX SMP Negeri 14 B.Aceh. Teknik pengambilan sampel menggunakan cluster random sampling dimana diperoleh siswa kelas IX A sebagai kelas eksperimen dan kelas IX B sebagai kelas kontrol. Hasil penelitian menunjukkan nilai rata-rata post-test untuk kelas eksperimen sebesar 77,5 dan untuk kelas kontrol sebesar 54,07. Hasil uji normalitas menunjukkan nilai X2hitung sebesar 2,7 untuk kelas eksperimen dan X2hitung 2,2 untuk kelas kontrol . Nilai X2tabel sebesar 5,9  pada taraf signifikan 0,05. Nilai X2hitung kurang dari X2tabel maka data terdistribusi normal. Hasil uji homogenitas kelas eksperimen dan kelas kontrol menunjukkan nilai  Fhitung sebesar 1,19 dan nilai Ftabel sebesar 1,85. Nilai kurang dari , maka kedua kelas homogen. Hasil uji-t pooled varians didapatkan nilai thitung sebesar 2,29 dan nilai t tabel sebesar 1,645 dengan taraf signifikan 0,05. Nilai lebih besar dari , maka Ho ditolak dan Ha diterima. Kesimpulan penelitian adalah terdapat pengaruh model pembelajaran SFAE dengan pendekatan active learning terhadap hasil belajar IPA siswa kelas IX IPA SMP Negeri 14 Banda Aceh.